The Blasting Works Effect Assessment Due to Highway Tunnel Construction - Valášková, Veronika; Papán, Daniel; Drusa, Marian (GeoScience Engineering, 2016)
Blasting works are one of the fundamental parts of daily Civil Engineering. Drilling and blasting still remain as the only possible way of tunnelling in highly unfavourable geological conditions. However, this method is a source of various disadvantages, the main one being tremors propagating through the geological environment which not only affect buildings, but also disturb the comfort of living in the vicinity of source. Designing of this procedure is mostly done using standardized empirical relations. This article shows the possibility of using FEM technique in predicting the effect of the blast. This approach is demonstrated in a simple case study on the impact of blasting works on steel pipe.